Atomistic simulations of the free-energy landscapes of interstellar chemical reactions: the case of methyl isocyanate. Issue 2 (9th April 2021) - Cassone, Giuseppe; Saija, Franz; Sponer, Jiri; Sponer, Judit E; Jiménez-Escobar, Antonio; Ciaravella, Angela; Cecchi-Pestellini, Cesare
ABSTRACT: Although complex organic molecules are observed in a wide variety of environments, chemical reaction networks heading to their formation are higly debated. It is a major endeavour to model the rates of reactions and incorporate them into chemical networks. The vast majority of the computational investigations in astrochemistry take into consideration oversimplified molecular models where chemical reactions are simulated under vacuum conditions (gas phase) and with crudely approximated entropic contributions to the free energy. We use density functional theory-based molecular dynamics techniques coupled with state-of-the-art metadynamics methods to investigate the role of ices embedding the reactants in shaping the free-energy landscape of selected reactions. Ices are chemically defined at the same level of theory of the reactants themselves. We consider as test case the transformation of methane and isocyanic acid into molecular hydrogen and methyl isocyanate, a species bearing similarities with peptide bonds. We examine the thermodynamically unfavoured case of very stable reactants to magnify modifications in the energy configuration induced by a solid amorphous water ice, either pure or mixed with CO. The presence of an active medium modifies significantly the free-energy surface, widening the path connecting reactants and products, and decreasing substantially the energy barriers. Ices not only act as gatherers of reactants, but also create thermodynamic conditions favouring chemical evolution.